Tinjauan Literatur tentang Peran Ekosistem Mangrove dalam Mendukung Kehidupan Alami Populasi Kepiting di Provinsi Gorontalo: Antara Konservasi dan Pemanfaatan Berkelanjutan - Eka Reza Saputra Widodo; Ardiansyah S. Akili; Yusfriandi Dwi Ariesna; Ramli Utina; Dewi Wahyuni K. Baderan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Mangrove ecosystems play a vital role in maintaining coastal environmental balance, providing habitats for various species, and supporting local livelihoods. In Gorontalo Province, the utilization of mangrove ecosystems faces significant challenges between conservation and sustainable exploitation. This study aims to review scientific literature discussing the use, degradation, and conservation efforts of mangroves in the region. The research method employed is a literature review analyzing 10 primary sources, including journals and books published within the last decade. The findings indicate that mangrove degradation in Gorontalo is caused by land conversion, overexploitation of resources, and weak local governance and regulations. On the other hand, there are promising initiatives such as ecotourism development and community-based management approaches that show potential for ensuring ecosystem sustainability. This study concludes that mangrove management strategies in Gorontalo must strengthen community participation, cross-sector integration, and adaptive policy approaches based on local conditions. Recommendations include improving institutional capacity and developing holistic policies that balance ecological and economic aspects.